Adsorption and Diffusion Behavior of Cl− on Sputtering Fe–20Cr Nanocrystalline Thin Film in Acid Solution (pH = 2). Issue 12 (December 2015) - Zhang, Bin; Liu, Li; Li, Tianshu; Li, Ying; Lei, Mingkai; Wang, Fuhui
Abstract : The adsorption and diffusion behavior of Cl − on sputtering Fe–20Cr nanocrystalline (NC) thin film compared with corresponding coarse crystalline (CC) alloy has been studied in HCl + NaCl solution (pH = 2, [Cl − ]=0.1 mol/L) by electrochemical techniques, X-ray photoelectron spectroscopy (XPS) and the first-principles calculations. The XPS results show that adsorption and diffusion of Cl − in the passive film has been inhibited on NC thin film. Ultra-violet photoelectron spectroscopy (UPS) results show that the work function Φ s of NC thin film (4.7 eV) is higher than that of CC alloy (4.5 eV). The theoretical calculations and valence electron structure analysis were used to understand the effect of nanocrystallization in this work.